Comparative morphology and transcriptome analysis reveals distinct functions of the primary and secondary laticifer cells in the rubber tree - Deguan Tan (Nature Portfolio, 2017)
Abstract Laticifers are highly specialized cells that synthesize and store natural rubber. Rubber trees (Hevea brasiliensis Muell. Arg.) contain both primary and secondary laticifers. Morphological and functional differences between the two types of laticifers are largely unknown, but such information is important for breeding and cultivation practices. Morphological comparison using paraffin sections revealed only distribution differences: the primary laticifers were distributed randomly, while the secondary laticifers were distributed in concentric rings. Using isolated laticifer networks, the primary laticifers were shown to develop via intrusive “budding” and formed necklace-like morphology, while the secondary laticifers developed straight and smooth cell walls. Comparative transcriptome analysis indicated that genes involved in cell wall modification, such as pectin esterase, lignin metabolic enzymes, and expansins, were highly up-regulated in the primary laticifers and correspond to its necklace-like morphology. Genes involved in defense against biotic stresses and rubber biosynthesis were highly up-regulated in the primary laticifers, whereas genes involved in abiotic stresses and dormancy were up-regulated in the secondary laticifers, suggesting that the primary laticifers are more adequately prepared to defend against biotic stresses, while the secondary laticifers are more adequately prepared to defend against abiotic stresses. Therefore, the two types of laticifers are morphologically and functionally distinct.